2018
DOI: 10.1371/journal.pone.0201613
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of NDM-1 and 5, and OXA-181 carbapenemases in uropathogenic Escherichia coli isolates from Riyadh, Saudi Arabia

Abstract: Urinary tract infections (UTIs) associated with Escherichia coli are a growing threat with an increase in the prevalence of multidrug resistant (MDR) strains, particularly ß-lactamase producers, occurring globally. We investigated the presence of carbapenem-resistant uropathogenic E. coli clones in community-acquired UTIs in Riyadh, Kingdom of Saudi Arabia (KSA) to identify the virulence and resistance structures of the resistant clones and relate the isolates to those circulating globally. A combination of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 63 publications
2
34
1
Order By: Relevance
“…Recently, a cluster of NDM-5 and chromosomally mediated OXA-181-producing pan-resistant K. pneumoniae from 4 patients in Abu Dhabi with possible connections to the strains subsequently isolated in South Korea, was reported by Sonnevend et al, 2017 [25]. However, finding this combination in E. coli, like ours, has only been reported once before in Egypt [43] and Saudi Arabia [44]. It should be noted that in our study this combination was also found in one S. boydii isolated from a patient with diabetes mellitus and ischemic heart disease in Adan hospital representing the first of such report in this bacterium particularly in this country and the region.…”
Section: Discussionsupporting
confidence: 55%
“…Recently, a cluster of NDM-5 and chromosomally mediated OXA-181-producing pan-resistant K. pneumoniae from 4 patients in Abu Dhabi with possible connections to the strains subsequently isolated in South Korea, was reported by Sonnevend et al, 2017 [25]. However, finding this combination in E. coli, like ours, has only been reported once before in Egypt [43] and Saudi Arabia [44]. It should be noted that in our study this combination was also found in one S. boydii isolated from a patient with diabetes mellitus and ischemic heart disease in Adan hospital representing the first of such report in this bacterium particularly in this country and the region.…”
Section: Discussionsupporting
confidence: 55%
“…Since 2014, the description of OXA-181 has escalated on a global scale, with reports from Asia (e.g., Japan [149], South Korea [150], China [151], Thailand [152], Pakistan [153], and Myanmar [154]), North America (e.g., the United States [155][156][157] and Canada [158]), Europe (e.g., Denmark [159], Austria [160], Switzerland [161], the Czech Republic [121], France [162], Poland [95], Italy [163], and Spain [164]), Africa (Burkina Faso [165], Egypt [166], Angola [167], Mali [168], Nigeria [169], and São Tomé and Príncipe [170]), the Middle East (e.g., Lebanon [171] and Saudi Arabia [172]), and Oceania (e.g., Australia [173]). Previous travel to India (147), Nigeria (174), and the Middle East (150) was identified as a risk factor of infection with OXA-181-producing bacteria.…”
Section: Geographical Distribution Of Oxa-181mentioning
confidence: 99%
“…As in other regions of the Kingdom, people from Aljouf routinely travel to Makkah for Umrah throughout the year. Various studies and reports from different regions of the Kingdom have highlighted the spread of resistant strains [37,[43][44][45][46]. Furthermore, the expatriate population may import and transmit Enterobacteriaceae with diverse resistance mechanisms [47] Aljouf has an expatriated population of 26% according to 2018 statistical data.…”
Section: Plos Onementioning
confidence: 99%